Relationship between presence of vasoconstrictor activity in cerebrospinal fluid and time after subarachnoid haemorrhage from rupture of cerebral arterial aneurysms. Issue 7 (July 1979) - Hunt, T M; Du Boulay, G H; Blaso, W P; Forster, D M; Boullin, D J
Abstract : The relationship between clinical condition and vasoconstrictor factors in cerebrospinal fluid was studied in 19 patients for up to six weeks after subarachnoid haemorrhage. Vasoconstrictor activity was assayed biologically. Sixteen of 19 patients improved as vasoconstrictor activity declined; this pattern was not significantly influenced by surgery. Serial angiography was performed on three patients and a qualitative relationship was shown between arterial dilatation, clinical improvement, and reduced pharmacological activity.